2018
DOI: 10.1111/jam.13942
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric bacterial isolates of grass pea (Lathyrus sativusL.) endowed with multiple plant growth promoting traits

Abstract: This study illustrates an effective alternative to conventional fertilizers that may contribute to crop disease reduction. Our results provide a foundation for future research that will lead to identifying potentially useful biocontrol strains found in the rhizosphere of grass pea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…In this study, the production of plant growth-promoting trait by Enterococcus spp. agreed with the study of (Anzuay et al 2017;Mussa et al 2018) that reported the isolation of Enterococcus spp growth-promoting potential and antifungal activity against pathogenic fungi from the rhizosphere of grass pea. Massilia spp.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the production of plant growth-promoting trait by Enterococcus spp. agreed with the study of (Anzuay et al 2017;Mussa et al 2018) that reported the isolation of Enterococcus spp growth-promoting potential and antifungal activity against pathogenic fungi from the rhizosphere of grass pea. Massilia spp.…”
Section: Discussionsupporting
confidence: 91%
“…No isolate produced IAA in physiologically relevant concentrations, in agreement with previous studies which also included also LAB [ 69 , 70 ]. On the other hand, Mussa et al [ 71 ] reported that one strain of Enterococcus casseliflavus , isolated from grass pea rhizospheric soil, synthesized IAA at a concentration of ca. 56 µg mL −1 , corresponding to about one order of magnitude higher than the best IAA producer among the LAB subjected to this research.…”
Section: Discussionmentioning
confidence: 99%
“…Under our experimental conditions, all the 16 LAB strains solubilized high amount of phosphate, comparable to strains of Enterococcus sp. isolated from grass pea rhizospheric soil [ 71 ]. The release of organic acids from LAB and the consequent acidification of broth (4.5 < pH < 4.9) could explain the observed solubilization of P. Indeed, previous researches showed inverse correlation between phosphate solubilization and pH of culture broth, varying from weak–moderate [ 71 ] to strong [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different proportions of grasspea protein isolates and glycerol were used to combine Lepidium perfoliatum L. seed gum to form composite biopolymer films that are biodegradable in nature ( 91 ). An effective biocontrol strain of plant growth promoting rhizobacteria obtained from the rhizosphere of grasspea was used as an alternative to conventional fertilizer that could contribute to crop disease reduction and significantly increase crop growth and yield ( 92 ). The ability of this crop to withstand nutrient shortage and retain vast amounts of lead in the root tissues has made it a tough species.…”
Section: Abandoned Neglected and Orphan Legume With Multiple Usesmentioning
confidence: 99%